Expression of p120-Catenin Isoforms Correlates with Genomic and Transcriptional Phenotype of Breast Cancer Cell Lines - Joana Paredes; Ana Luísa Correia; Ana Sofia Ribeiro; Fernando Schmitt (Cellular Oncology)
Background: P120-catenin is a member of the Armadillo protein family, which is involved in intercellular adhesion and cell signalling. It directly interacts with the classical cadherins juxtamembrane domain and contributes for both junction formation and its disassembly. Accumulating evidences indicate that p120-catenin is important in tumour formation and progression, although the role of their multiple spliced isoforms in the regulation of cadherin-mediated adhesion of malignant cells is still not well understood. We investigated the expression of p120-catenin isoforms in a collection of breast cancer cell lines with distinct molecular profiles and expressing different cadherins. Methods: We assessed the expression by RT-PCR and Western-blotting analysis. Results: We observed that the expression of p120-catenin isoforms was associated with the genomic and transcriptional phenotype of breast cancer cells. Besides, the recruitment of p120-catenin isoforms was not apparently related with the particular expression of E-, P- or N-cadherin. Conclusion: We demonstrate that mammary tumour cells exhibit a characteristic p120-catenin isoform expression profile, depending from their specific genomic and transcriptional properties. These particular expression patterns, combined with other regulatory proteins and in a specific cellular context, may explain how p120-catenin can either contribute to strength intercellular adhesions or instead to promote cell motility.